Lecture hall chair : an ergonomics approach - Mohd Asrol, Adnan (2009)
This project is to investigate how students that use Universiti Malaysia Pahang lecture hall chair are having problems such as back pain and find the sources of this problem. I have analyses the chairs at lecture hall and investigate to know the criteria that brought the entire problem to the students. For the first step, I do some literature review about the chair based on an ergonomics approach. I have determined the criteria that should have in a chair and suitable of human body follow on ergonomics type. A suggested of an ergonomics lecture hall chair for students will be carried out after the analysis of survey data that have collected from the students. The survey data would be gained from questionnaires distributed to selected correspondences. After done the investigation, I surely know the non-ergonomics criteria that have in UMP lecture hall chairs. Finally, I will come out the suggestion to improve the comfortable of the lecture hall chairs.